2021
DOI: 10.1186/s13643-021-01633-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gut microbiota modulation on feeding tolerance of enterally fed critically ill adult patients: a systematic review

Abstract: Purpose The objective of this systematic review was to evaluate the effect of pre-, pro-, and synbiotics on feeding tolerance of enterally fed critically ill adult patients. Methods MEDLINE, Science Direct, Web of Knowledge, and the Cochrane Central Register of Controlled Trials were searched up to November 2019. English language randomized controlled trials reporting the effect of pre, pro or synbiotics on the feeding tolerance of enterally fed cr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 43 publications
1
11
1
Order By: Relevance
“…Although enteral feed volume, energy, and protein intake increased signi cantly during the rst four days in the synbiotic group, the overall changes were not signi cant and there was no difference in the total EN volume and energy or protein intake between the two groups. Our recent systematic review also showed that synbiotic, probiotic or prebiotic does not affect energy intake and feed volume in tube-fed critically ill patients (21). Although, Rushdi et al showed that prebiotic supplementation was associated with signi cantly increased feed volume on day 4 the intervention group (22), which was inconsistent with our results.…”
Section: Discussioncontrasting
confidence: 91%
“…Although enteral feed volume, energy, and protein intake increased signi cantly during the rst four days in the synbiotic group, the overall changes were not signi cant and there was no difference in the total EN volume and energy or protein intake between the two groups. Our recent systematic review also showed that synbiotic, probiotic or prebiotic does not affect energy intake and feed volume in tube-fed critically ill patients (21). Although, Rushdi et al showed that prebiotic supplementation was associated with signi cantly increased feed volume on day 4 the intervention group (22), which was inconsistent with our results.…”
Section: Discussioncontrasting
confidence: 91%
“…The full extent of the implications of gut microbiome composition in the intensive care setting is beyond the scope of this review and has been thoroughly discussed elsewhere. [79][80][81] Nevertheless, several examples will be reviewed here.…”
Section: Gut Microbiome In Intensive Carementioning
confidence: 99%
“…Although enteral feed volume, energy, and protein intake increased significantly during the first 4 days in the synbiotic group, the overall changes were not significant, and there was no difference in the total EN volume and energy or protein intake between the two groups. Our recent systematic review also showed that synbiotic, probiotic, or prebiotic does not affect energy intake and feed volume in tube-fed critically ill patients [ 23 ]. Although, Rushdi et al showed that prebiotic supplementation was associated with significantly increased feed volume on day 4 in the intervention group [ 24 ], which was inconsistent with our results.…”
Section: Discussionmentioning
confidence: 99%